GARCÍA MARQUÉS, A. (2019). Pensando el sujeto: Aristóteles y Quine. Madrid: Dykinson. - Haro Almansa, Francisco Andrés (Daimon Revista Internacional de Filosofia, 2024)
Reseña de: GARCÍA MARQUÉS, A. (2019). Pensando el sujeto: Aristóteles y Quine. Madrid: Dykinson.